Reversibility of β-Cell-Specific Transcript Factors Expression by Long-Term Caloric Restriction in db/db Mouse - Chunjun Sheng; Feng Li; Ziwei Lin; Manna Zhang; Peng Yang; Le Bu; Hui Sheng; Hong Li; Shen Qu (Journal of Diabetes Research)
Type 2 diabetes (T2D) is characterized by β-cell dedifferentiation, but underlying mechanisms remain unclear. The purpose of the current study was to explore the mechanisms of β-cell dedifferentiation with and without long-term control of calorie intake. We used a diabetes mouse model (db/db) to analyze the changes in the expression levels of β-cell-specific transcription factors (TFs) and functional factors with long-term caloric restriction (CR). Our results showed that chronic euglycemia was maintained in the db/db mice with long-term CR intervention, and β-cell dedifferentiation was significantly reduced. The expression of Glut2, Pdx1, and Nkx6.1 was reversed, while MafA expression was significantly increased with long-term CR. GLP-1 pathway was reactivated with long-term CR. Our work showed that the course of β-cell dedifferentiation can intervene by long-term control of calorie intake. Key β-cell-specific TFs and functional factors play important roles in maintaining β-cell differentiation. Targeting these factors could optimize T2D therapies.